Paraneoplastic anti-Yo antibody mediated subacute cerebellar degeneration. Case series and literature review - M. Vaišvilas; R. Mameniškienė; A. Barkauskienė (Neurologijos seminarai)
Paraneoplastic neurologic syndromes are a subgroup of diseases due to indirect cytotoxic effects of the immune system on specific brain structures rather than the mass effect itself. Paraneoplastic anti-Yo antibody mediated subacute cerebellar degeneration is characterised by an insidious onset, a characteristic neurologic syndrome of cerebellar dysfunction, normal or near/normal brain imaging on MRI, and gynaecologic malignancies identified by thorough investigation in middle aged post-menopausal women. Despite various aggressive treatments available, the prognosis is often considered poor. We present two cases with classical findings consistent with paraneoplastic subacute cerebellar degeneration and give literature review.